Anticancer effect of buddlejasaponin IV and buddlejasaponin IVa from Clinopodium umbrosum on oral cancer cells (HN-5). (December 2022) - Sharifi, Simin; Naseri, Negar; Fathiazad, Fatemeh; Asnaashari, Solmaz; Hamedeyazdan, Sanaz
Abstract: Purpose: Due to the existence of bioactive compounds with different biological activity in the genus Clinopodium; C. umbrosum was selected to evaluate its cell toxicity. Methods: C. umbrosum aerial parts were solvent extracted and extracts were fractionated via various chromatographic techniques, so as to obtain two pure saponins, buddlejasaponin IVa and buddlejasaponin IV. The cytotoxicity activity of the extracts and the two pure compounds on oral cancer cells (HN-5) and human umbilical vein endothelial cells (HUVECs) were investigated by 3-(4, 5-Dimethylthiazol-2-Yl)-2, 5-Diphenyltetrazolium Bromide (MTT) method. To evaluate the effect on apoptosis induction, HN-5 cells were treated for 24 h and studied by FITC Annexin V/PI staining using flow cytometry. Subsequently, the apoptosis pathway was studied through real-time RT PCR. Besides, the scratch test was performed to study the cell migration. Results: The cytotoxic activity of petroleum ether, chloroform and methanol extracts on HN-5 oral cancer cells after 24 h of treatment was calculated with IC50 values of >250, >167 and 239.5 μg/mL, respectively. The cytotoxic findings for buddlejasaponin IVa and buddlejasaponin IV showed that buddlejasaponin IV possessed superior cytotoxicity whilst both compounds showed their cytotoxicity through the apoptotic pathway with increasing Bax/Bcl2 ratio and the level of caspase 9 . Also, HN-5 cells migration was reduced with two saponin compounds. Conclusion: C. umbrosum possessed significant cytotoxicity on HN-5 cells and the mechanism of cytotoxicity for its two major compounds, buddlejasaponin IVa and buddlejasaponin IV, was identified as the mitochondrial pathway of apoptosis reducing the invasive potential of HN-5 cells. Graphical abstract: Image 1 Highlights: Cytotoxic saponins, buddlejasaponin IV and buddlejasaponin IVa were isolated from Clinopodium umbrosum . Buddlejasaponin IV and buddlejasaponin IVa inducted the mitochondrial pathway of apoptosis. Buddlejasaponin IV and buddlejasaponin IVa reduced the metastasis of oral cancer cell line. The highest cytotoxicity was observed from buddlejasaponin IV on oral cancer cell line.